Market survey for organic foods from CARICOM countries in selected European countries (United Kingdom, France and Germany) - Baccus, Earle C. ([Caribbean Regional Negotiating Machinery] [Christ Church]BB, 2001)
Identifies organic products from CARICOM countries with a view to exploiting existing and potential export opportunities in the United Kingdom, France and Germany.